Mutual Coupling Reduction in Patch Antenna Arrays by Using a Planar EBG Structure and a Multilayer Dielectric Substrate - Rajo-Iglesias, E.; Quevedo-Teruel, O.; Inclan-Sanchez, L. (IEEE transactions on antennas and propagation, 2008)
Periodic structures can help in the reduction of mutual coupling by using their capability of suppressing surface waves propagation in a given frequency range. The purpose of this work is to show the viability of using a planar electromagnetic band gap (EBG) structure based on a truncated frequency selective surface (FSS) grounded slab to this aim. The goal is to use it in patch antenna arrays, keeping both the element separation smaller than for grating lobes avoidance (assuming broadside case) and the patch antenna size large enough to have a good antenna directivity. To this aim, a multilayer dielectric substrate composed of high and low permittivity layers is convenient. This allows the use of a planar EBG structure made of small elements printed on the high permittivity material and, at the same time, the low permittivity layer helps the bandwidth and the directivity of the antenna to be increased. The EBG structure was designed under these premises and optimized for the particular application via an external optimization algorithm based on evolutionary computation: ant colony optimization (ACO). The mutual coupling reduction has been measured and it is larger than 10 dB with a completely planar structure.